Sun Performance and Tuning Java™ and the Internet, Second Edition - Cockcroft, Adrian; Pettit, Richard (Pearson, 1998)
9524J-6 "As practical as a Swiss Army knife for a power-hungry SysAdmin. For all the Sun gurus, veterans and newbies: This is for you. As a must-have in one's library, it'll be one of your most worn out references in your serious IT career. It is practical and very illustrative in its approach to solving sample problems." -Dexter D. Laggui Hailed in its first edition as an indispensable reference for system administrators, Sun Performance and Tuning has been revised and expanded to cover Solaris 2.6, the newest generation of SPARC hardware, and the latest Internet and Java server technologies. Featuring a quick guide to get you started, as well as detailed reference information, this book is indispensable both for developers who need to design for speed and administrators who need to manage system and network performance. Performance guru Adrian Cockcroft brings his unique expertise and structured approach to this complex and rapidly changing topic, providing detailed information on key aspects of performance management and system behavior that is not available anywhere else. Rich Pettit, author of the SE performance toolkit, describes the performance interfaces in Solaris and how to use this freely available toolkit to build your own customized performance-monitoring tools. Key topics covered include: Performance Management and Measurement TCP and Internet Server Tuning JAVA Network Computer Server Sizing SPARC System Architectures Kernel Algorithms and Tuning How to Build Your Own Performance Tools Performance Rules and the virtual_adrian SE Tool To get up to speed quickly on critical performance issues, this is the one book any Sun administrator, integrator or developer needs.
Online resource; Title from title page (viewed April 7, 1998)
Keywords: Sun computers; Internet; Java (Computer program language); Sun (Ordinateurs); Java (Langage de programmation)